Pengaruh Segmentasi Pasar terhadap Tingkat Penjualan Produk Sumpia Syasyiri di Industri UMKM Banjaran Bandung - Setiawan, Iwan; Tiris Sudrartono (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study wants to find out how much the attractiveness of the business sector is for MSME products such as sumpia syasyiri in Banjaran, Bandung City. The reason for this research refers to SMEs in selling their products which have not been maximized in terms of relatively large sales for this Syasyiri sumpia product. This research uses a type of quantitative research with descriptive research. The investigative technique used is Cronbach's Alpha and the tests used are validity test, reliability test, correlation coefficient test and speculation test. Statistical Product and Service Solution (SPSS) Version 25 which was used to test this research. the results of this study, researchers provide suggestions for SMEs so that their products can be marketed to reach better market conditions through marketplaces such as shopee, lazada, or tokopedia so that there is a product promotion system, provide lower selling prices, provide updates for business people to look innovative, and lastly, maximize orders so that sales levels also increase for Banjaran Bandung Sumpia Syasyiri products.